Comparison of the Strength of Musculus Flexores Superior Extremities Against Pre-Elderly Men and Male College Students - Budi, Budi Irawan Habibi; Soekanto, Ayly; Ernawati, Sie (Calvaria Medical Journal, 2025)
Background: Muscle strength is a force released by a muscle or group of muscles used to perform an activity. Everyone has different daily activities and activities so that not everyone has the same muscle strength. It is very common for pre-elderly to experience decreased muscle mass and muscle strength, decreased muscle volume with age and replaced by fat tissue and connective tissue. Purpose: This study was to measure the strength of the superior extremity flexor muscles in male pre-elderly and male students. The tool used was a handgrip dynamometer. Method: This study used an observational design with a cross-sectional approach with a research sample of 30 people divided into two groups of 15 male pre-elderly and 15 male students who had muscle strength measurements then the data was applied to SPPS 29. Results: The results of the strength of the superior extremity flexor muscles in male pre-elderly were 27.82 kilogram and in male students were 28.00 kilogram. Conclusion: The strength of the superior extremity flexor muscles in male students was proven to be stronger than that of male pre-elderly